2020
DOI: 10.3390/ijms21113919
|View full text |Cite
|
Sign up to set email alerts
|

Combined Optimization of Codon Usage and Glycine Supplementation Enhances the Extracellular Production of a β-Cyclodextrin Glycosyltransferase from Bacillus sp. NR5 UPM in Escherichia coli

Abstract: Two optimization strategies, codon usage modification and glycine supplementation, were adopted to improve the extracellular production of Bacillus sp. NR5 UPM β-cyclodextrin glycosyltransferase (CGT-BS) in recombinant Escherichia coli. Several rare codons were eliminated and replaced with the ones favored by E. coli cells, resulting in an increased codon adaptation index (CAI) from 0.67 to 0.78. The cultivation of the codon modified recombinant E. coli following optimization of glycine supplementation enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Codon usage is critical to achieving adequate protein expression levels in E. coli [32], [33]. This technique can improve the production of various recombinant proteins expressed by E. coli [34], [35], [36]. Blastx analysis from the SEBsyn consensus sequence was showed that this sequence has specific hits with SEB protein sequences in the database with identities ranging about 97-100 %.…”
Section: Resultsmentioning
confidence: 99%
“…Codon usage is critical to achieving adequate protein expression levels in E. coli [32], [33]. This technique can improve the production of various recombinant proteins expressed by E. coli [34], [35], [36]. Blastx analysis from the SEBsyn consensus sequence was showed that this sequence has specific hits with SEB protein sequences in the database with identities ranging about 97-100 %.…”
Section: Resultsmentioning
confidence: 99%
“…We first evaded expression problems due to codon bias (incompatibility of codon usage between human sTNF-α gene and E. coli CFPS system) via computational optimization of the codon profile of the human sTNF-α gene as previously described for human sTNF-α and other recombinant proteins [ 7 , 22 , 36 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminally attached His6-tag is the common design for a nity puri cation of the extracellularly produced proteins [6][7][8][9][10][11]. In a few cases, the His6-tag is incorporated between the target protein and Cterminal signal peptide [12], or fused to the N-terminus of the target protein [13,14], for purifying the protein secreted into the culture. The a nity tags including glutathione S-transferase (GST) as the Cterminal fusion partner, and maltose binding protein as the N-terminal carrier are occasionally used for rapid puri cation of the produced proteins of interest via extracellular production [15,16].…”
Section: Introductionmentioning
confidence: 99%